Thermal insulation coating and preparation method thereof
By introducing modified graphene oxide and modified hollow glass microbeads into the thermal insulation coating, the problem of degradation of fluidity and construction performance caused by high proportion of titanium dioxide in existing thermal insulation coatings is solved, and better thermal insulation effect is achieved. Anti-aging properties.
Patent Information
- Application Number
- CN202510043154.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
In the use of high proportion of titanium dioxide, existing thermal insulation coatings have reduced film fluidity and construction performance, and there is a risk of peeling, and there is still room for improvement in thermal insulation and aging resistance.
Modified graphene oxide and modified hollow glass microbeads are used to increase its hydrophilicity by 1-amino-8-naphthol-3,6-disulfonic acid, and trimethyltrivinyl Cyclotrisilane performs surface grafting of hollow glass microbeads to improve their dispersion and interface compatibility in thermal insulation coatings.
It improves the thermal stability and thermal conductivity of thermal insulation coatings, maintains good mechanical properties and thermal stability, achieves excellent thermal insulation effects, and significantly improves anti-aging performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal insulation coatings, and specifically relates to a thermal insulation coating and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of world science and technology and social production, people have become increasingly aware that environmental and energy issues have become urgent problems to be solved in this century. Therefore, energy conservation has become a long-term strategic policy for my country's economic development.
[0003] When an object absorbs the sun's radiation, its surface temperature will rise, which brings many inconveniences to daily life and industrial production. The temperature rise of the exterior wall surface and the building roof will cause the surrounding environment and indoor temperature to be too high. In order to alleviate the continuous increase in temperature, the power consumption of refrigeration equipment such as air conditioners and refrigerators will inevitably increase; and thermal insulation coatings can save energy and prevent environmental pollution. It is precisely because of the role of thermal insulation coatings in energy saving and environmental protection that the research and application of thermal insulation technology has received increasing attention; a lot of research has been conducted on thermal insulation coatings at home and abroad, and many research results have been successfully industrialized.
[0004] For example, the Chinese invention patent with application number: CN201610446861.1 discloses a heat-reflective insulation coating for recoating the exterior walls of buildings and a preparation method thereof, which is characterized in that it is made of the following components in parts by weight: 15 to 20 parts of alcohol-soluble acrylic resin A, 30 to 35 parts of alcohol-soluble acrylic resin B, 20 to 25 parts of titanium dioxide, 4 to 6 parts of hollow glass microspheres, 8 to 12 parts of hollow ceramic microspheres, 0.5 to 1 part of silane coupling agent, 0.5 to 0.8 parts of dispersant, 0.3 to 0.5 parts of defoaming agent, 0.2 to 0.6 parts of leveling agent, and 8 to 14 parts of isopropyl alcohol.
[0005] In the above-mentioned prior art, a large amount of titanium dioxide is added to the coating, which can increase the whiteness and hiding power of the coating film. However, a high proportion of titanium dioxide will affect the fluidity and construction performance of the coating, and may make the coating film more fragile and easy to peel off; especially when it is used in the exterior walls of buildings, there is a risk of peeling, which will cause great safety hazards. In addition, the thermal insulation performance and artificial aging resistance of the above-mentioned prior art still have a lot of room for improvement.
[0006] Therefore, there is an urgent need to introduce new process technologies to solve the above problems and seek more feasible solutions. Summary of the invention
[0007] In order to solve the defects existing in the above technical scheme, the purpose of the present invention is to provide a thermal insulation coating and a preparation method thereof; the purpose of the present invention can be achieved by the following technical scheme: a thermal insulation coating, calculated by weight, is composed as follows: 10 to 30 parts of deionized water, 20 to 30 parts of binder, 15 to 36 parts of filler, 2 to 5 parts of nano-composite ingredients, 2 to 6 parts of modified graphene oxide, 5 to 10 parts of modified hollow glass microspheres, 1 to 2 parts of freeze-thaw agent, 1 to 3 parts of film-forming agent, 0.2 to 0.6 parts of defoaming agent, 0.1 to 0.3 parts of dispersant, and 0.3 to 0.6 parts of thickener.
[0008] The adhesive is a mixture of pure acrylic emulsion and styrene acrylic emulsion; The filler is a mixture of titanium dioxide, sericite and talc, and the mass ratio of the three is (10-22): (3-8): (2-6); The nano composite material is nano-scale SiO 2 The mass ratio of the mixture with nano Zn is 1:1; The freeze-thaw agent is any one of ethylene glycol or propylene glycol; The film-forming agent is any one of dodecyl alcohol ester and hexanediol butyl ether acetate; The defoamer is any one of BYK-A555 defoamer, GP330 defoamer and BNK-G303 defoamer; The dispersant is: any one of Allnex6208 dispersant and UNIQSPERSE 586U dispersant; The thickener is any one of hydroxypropyl methylcellulose and hydroxyethyl cellulose.
[0009] The preparation and synthesis method of the modified graphene oxide is as follows: dispersing graphite oxide in 250 ml of deionized water and ultrasonically treating for 1 hour; dissolving 1-amino-8-naphthol-3,6-disulfonic acid in 10 ml of deionized water and dropping 2-3 drops of ammonia solution; then slowly dropping the mixed solution into the fully dispersed graphite oxide; and fully stirring; after all the additions, heating to 70 degrees Celsius and stirring for 24 hours; after the stirring is completed, adding hydrazine hydrate and heating to 100 degrees Celsius; continuing to stir for 24 hours; then naturally cooling the solution to room temperature, filtering with cellulose acetate membrane filter paper with a pore size of 0.1 micrometers, and washing with distilled water for multiple times to obtain a water-dispersed black product, and finally drying the black product in a vacuum at 60 degrees Celsius for 72 hours to prepare the homemade modified graphene oxide.
[0010] The preparation and synthesis method of the modified hollow glass microspheres is as follows: deionized water, hydrochloric acid, trimethyltrivinylcyclotrisilane, hollow glass microspheres, and ethanol are added together into a three-necked flask, and continuous mechanical and ultrasonic stirring is performed, and the reaction is carried out and maintained at 40 degrees Celsius for 5 hours; then the product obtained by the reaction is washed in ethanol and deionized water for two rounds respectively, and then dispersed; finally, the obtained product is dried at 100 degrees Celsius for 5 hours to prepare the modified hollow glass microspheres.
[0011] A method for preparing a thermal insulation coating comprises: firstly physically stirring and mixing a nano-composite ingredient, modified graphene oxide, modified hollow glass microspheres and a filler to prepare a mixture A for standby use; then adding deionized water, a binder, a filler, a freeze-thaw agent, a film former, a defoamer and a dispersant into a stainless steel stirring tank, mixing for 2 hours, and the mixing stirring speed is 800-1200r / min; then adding the mixture A into the stainless steel stirring tank, and the stirring speed is 400-600r / min; then adding a thickener and continuously stirring for 1 hour; finally filtering the coating through a 100-120 mesh sieve to prepare the thermal insulation coating.
[0012] The present invention has the beneficial effects: 1. The present invention functionalizes graphene oxide by introducing 1-amino-8-naphthol-3,6-disulfonic acid for modification. The added sulfonic acid group and hydroxyl group after modification increase the hydrophilicity of the functionalized graphene oxide, so that it has better dispersibility in the thermal insulation coating, and 1-amino-8-naphthol-3,6-disulfonic acid is attached to the surface of graphene. This attachment can help prevent the aggregation of graphene sheets, maintain the two-dimensional structure and performance of the functionalized graphene oxide, and help improve the thermal stability of the thermal insulation material; 2. The present invention modifies hollow glass microspheres by using trimethyltrivinylcyclotrisilane as a surface grafting agent, thereby successfully grafting double bonds on the surface of the glass microspheres, making the surface properties of the hollow glass microspheres more compatible with the base material of the thermal insulation coating, thereby improving the interfacial compatibility of the coating; and forming a strong interfacial interaction between the coating substrate and the modified hollow glass microspheres; 3. In the present invention, modified graphene oxide and modified hollow glass microspheres are introduced into the thermal insulation coating at the same time; the two work synergistically, wherein the modified graphene oxide enhances the thermal stability of the thermal insulation coating, while the modified hollow glass microspheres enhance the thermal insulation coating's performance in blocking heat conduction. Under the synergistic effect of the two, the thermal insulation coating can avoid excessive heat conduction transfer, and can still maintain good mechanical properties and thermal stability at higher temperatures, thereby achieving a more excellent thermal insulation effect; and under the synergistic effect of the two, the anti-aging performance of the thermal insulation coating can also be significantly improved. DETAILED DESCRIPTION
[0013] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment, and the illustrative embodiments of the present invention and its description are only used to explain the present invention, and are not used as limitation of the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper limit and the lower limit of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper limit and lower limit of these smaller ranges can be independently included or excluded in the scope.
[0014] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0015] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0016] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0017] The "parts" indicated in the following examples are all parts by weight.
[0018] Example 1 A thermal insulation coating comprises the following ingredients, measured by weight: 10 parts of deionized water, 20 parts of a binder, 15 parts of a filler, 2 parts of a nano-composite material, 2 parts of modified graphene oxide, 5 parts of modified hollow glass microspheres, 1 part of a freeze-thaw agent, 1 part of a film-forming agent, 0.2 parts of a defoaming agent, 0.1 parts of a dispersant, and 0.3 parts of a thickener.
[0019] The adhesive is a mixture of pure acrylic emulsion and styrene acrylic emulsion; The filler is a mixture of titanium dioxide, sericite and talcum powder, and the mass ratio of the three is 10:3:2; The nano composite material is nano-scale SiO 2 The mass ratio of the mixture with nano Zn is 1:1; The freeze-thaw agent is ethylene glycol; The film-forming agent is dodecyl alcohol ester; The defoamer is BYK-A555 defoamer; The dispersant is Allnex6208 dispersant; The thickener is hydroxypropyl methylcellulose.
[0020] The preparation and synthesis method of the modified graphene oxide is as follows: 500 mg of graphite oxide is dispersed in 250 ml of deionized water, and ultrasonically treated for 1 hour; 2.3 g of 1-amino-8-naphthol-3,6-disulfonic acid is dissolved in 10 ml of deionized water, and 2-3 drops of ammonia solution with a concentration of 1 mol / L are added; then the mixed solution is slowly added to the fully dispersed graphite oxide; and fully stirred. After all the additions are completed, the temperature is raised to 70 degrees Celsius and stirred for 24 hours; after the stirring is completed, 5 ml of hydrazine hydrate is added and the temperature is raised to 100 degrees Celsius; stirring is continued for 24 hours; then the solution is naturally cooled to room temperature, and filtered with a cellulose acetate membrane filter paper with a pore size of 0.1 microns, and washed with distilled water for multiple times (to remove 1-amino-8-naphthol-3,6-disulfonic acid that may not have reacted completely), to obtain a water-dispersed black product, and then the black product is dried in a vacuum at 60 degrees Celsius for 72 hours, that is, the homemade modified graphene oxide is prepared.
[0021] The preparation and synthesis method of the modified hollow glass microspheres is as follows: 400 g of deionized water, 3 ml of hydrochloric acid, 11 g of trimethyltrivinylcyclotrisilane, 10 g of hollow glass microspheres, and 5 ml of ethanol are added together into a three-necked flask, and continuous mechanical and ultrasonic stirring is performed, and the reaction is carried out and maintained at 40 degrees Celsius for 5 hours; then the product obtained by the reaction is washed in ethanol and deionized water for two rounds respectively, and then dispersed; finally, the obtained product is dried at 100 degrees Celsius for 5 hours to prepare the modified hollow glass microspheres.
[0022] In a specific implementation, the hollow glass beads are soda lime borosilicate glass; During specific implementation, the mass fraction of the hydrochloric acid is 36%.
[0023] A method for preparing a thermal insulation coating comprises: firstly physically stirring and mixing a nano-composite ingredient, modified graphene oxide, modified hollow glass microspheres and a filler to prepare a mixture A for standby use; then adding deionized water, a binder, a filler, a freeze-thaw agent, a film former, a defoamer and a dispersant into a stainless steel stirring tank, mixing for 2 hours, and the mixing stirring speed is 800-1200r / min; then adding the mixture A into the stainless steel stirring tank, and the stirring speed is 400-600r / min; then adding a thickener and continuously stirring for 1 hour; finally filtering the coating through a 100-120 mesh sieve to prepare the thermal insulation coating.
[0024] Example 2 A thermal insulation coating comprises the following ingredients, measured by weight: 14 parts of deionized water, 22 parts of a binder, 19 parts of a filler, 3 parts of a nano-composite material, 3 parts of modified graphene oxide, 6 parts of modified hollow glass microspheres, 1 part of a freeze-thaw agent, 1 part of a film-forming agent, 0.3 parts of a defoaming agent, 0.1 parts of a dispersant, and 0.3 parts of a thickener.
[0025] The adhesive is a mixture of pure acrylic emulsion and styrene acrylic emulsion; The filler is a mixture of titanium dioxide, sericite and talc, and the mass ratio of the three is 12:4:3; The nano composite material is nano-scale SiO 2 The mass ratio of the mixture with nano Zn is 1:1; The freeze-thaw agent is propylene glycol; The film-forming agent is dodecyl alcohol ester; The defoamer is GP330 defoamer; The dispersant is UNIQSPERSE 586U dispersant; The thickener is hydroxypropyl methylcellulose.
[0026] Among them, in Example 2, the preparation method of modified graphene oxide, the preparation method of modified hollow glass microspheres, and the preparation method of thermal insulation coating are all consistent with Example 1.
[0027] Example 3 A thermal insulation coating comprises the following ingredients, measured by weight: 18 parts of deionized water, 24 parts of a binder, 22 parts of a filler, 3 parts of a nano-composite material, 4 parts of modified graphene oxide, 7 parts of modified hollow glass microspheres, 1 part of a freeze-thaw agent, 2 parts of a film-forming agent, 0.4 parts of a defoaming agent, 0.2 parts of a dispersant, and 0.4 parts of a thickener.
[0028] The adhesive is a mixture of pure acrylic emulsion and styrene acrylic emulsion; The filler is a mixture of titanium dioxide, sericite and talc, and the mass ratio of the three is 14:4:4; The nano composite material is nano-scale SiO 2 The mass ratio of the mixture with nano Zn is 1:1; The freeze-thaw agent is propylene glycol; The film-forming agent is hexanediol butyl ether acetate; The defoamer is any one of the BNK-G303 defoamers; The dispersant is Allnex6208 dispersant; The thickener is hydroxyethyl cellulose.
[0029] Among them, in Example 3, the preparation method of modified graphene oxide, the preparation method of modified hollow glass microspheres, and the preparation method of thermal insulation coating are all consistent with Example 1.
[0030] Example 4 A thermal insulation coating comprises the following ingredients, measured by weight: 22 parts of deionized water, 26 parts of a binder, 28 parts of a filler, 4 parts of a nano-composite material, 5 parts of modified graphene oxide, 8 parts of modified hollow glass microspheres, 2 parts of a freeze-thaw agent, 2 parts of a film-forming agent, 0.5 parts of a defoaming agent, 0.2 parts of a dispersant, and 0.5 parts of a thickener.
[0031] The adhesive is a mixture of pure acrylic emulsion and styrene acrylic emulsion; The filler is a mixture of titanium dioxide, sericite and talc, and the mass ratio of the three is 18:6:4; The nano composite material is nano-scale SiO 2 The mass ratio of the mixture with nano Zn is 1:1; The freeze-thaw agent is ethylene glycol; The film-forming agent is dodecyl alcohol ester; The defoamer is BYK-A555 defoamer; The dispersant is UNIQSPERSE 586U dispersant; The thickener is hydroxypropyl methylcellulose.
[0032] Among them, in Example 4, the preparation method of modified graphene oxide, the preparation method of modified hollow glass microspheres, and the preparation method of thermal insulation coating are all consistent with Example 1.
[0033] Example 5 A thermal insulation coating comprises the following ingredients, measured by weight: 26 parts of deionized water, 28 parts of a binder, 32 parts of a filler, 4 parts of a nano-composite material, 5 parts of modified graphene oxide, 9 parts of modified hollow glass microspheres, 2 parts of a freeze-thaw agent, 3 parts of a film-forming agent, 0.6 parts of a defoaming agent, 0.3 parts of a dispersant, and 0.5 parts of a thickener.
[0034] The adhesive is a mixture of pure acrylic emulsion and styrene acrylic emulsion; The filler is a mixture of titanium dioxide, sericite and talc, and the mass ratio of the three is 20:6:6; The nano composite material is nano-scale SiO 2 The mass ratio of the mixture with nano Zn is 1:1; The freeze-thaw agent is propylene glycol; The film-forming agent is hexanediol butyl ether acetate; The defoamer is GP330 defoamer; The dispersant is UNIQSPERSE 586U dispersant; The thickener is hydroxypropyl methylcellulose.
[0035] Among them, in Example 5, the preparation method of modified graphene oxide, the preparation method of modified hollow glass microspheres, and the preparation method of thermal insulation coating are all consistent with Example 1.
[0036] Example 6 A thermal insulation coating comprises the following ingredients, measured by weight: 30 parts of deionized water, 30 parts of a binder, 36 parts of a filler, 5 parts of a nano-composite material, 6 parts of modified graphene oxide, 10 parts of modified hollow glass microspheres, 2 parts of a freeze-thaw agent, 3 parts of a film-forming agent, 0.6 parts of a defoaming agent, 0.3 parts of a dispersant, and 0.6 parts of a thickener.
[0037] The adhesive is a mixture of pure acrylic emulsion and styrene acrylic emulsion; The filler is a mixture of titanium dioxide, sericite and talc, and the mass ratio of the three is 22:8:6; The nano composite material is nano-scale SiO 2 The mass ratio of the mixture with nano Zn is 1:1; The freeze-thaw agent is propylene glycol; The film-forming agent is hexanediol butyl ether acetate; The defoamer is BYK-A555 defoamer; The dispersant is UNIQSPERSE 586U dispersant; The thickener is hydroxyethyl cellulose.
[0038] Among them, in Example 6, the preparation method of modified graphene oxide, the preparation method of modified hollow glass microspheres, and the preparation method of thermal insulation coating are all consistent with Example 1.
[0039] Comparative Example 1 A thermal insulation coating comprises the following ingredients, measured by weight: 22 parts of deionized water, 26 parts of a binder, 28 parts of a filler, 4 parts of a nano-composite material, 5 parts of graphene oxide, 8 parts of hollow glass microspheres, 2 parts of a freeze-thaw agent, 2 parts of a film-forming agent, 0.5 parts of a defoaming agent, 0.2 parts of a dispersant, and 0.5 parts of a thickener.
[0040] This comparative example 1 is based on Example 4, except that the 5 parts of graphene oxide and 8 parts of hollow glass microspheres in the formula are not subjected to the modification operation in Examples 1-6, but are directly added; except for the above-mentioned different formulas, the preparation method of the thermal insulation coating is the same as that of Example 4.
[0041] Comparative Example 2 A thermal insulation coating comprises the following ingredients, measured by weight: 22 parts of deionized water, 26 parts of a binder, 28 parts of a filler, 4 parts of a nano-composite material, 5 parts of modified graphene oxide, 8 parts of hollow glass microspheres, 2 parts of a freeze-thaw agent, 2 parts of a film-forming agent, 0.5 parts of a defoaming agent, 0.2 parts of a dispersant, and 0.5 parts of a thickener.
[0042] This comparative example 2 is based on Example 4, except that the hollow glass microspheres are not subjected to the modification operation in Examples 1-6, but are directly incorporated; except for the above-mentioned different formulas, the preparation method of the modified graphene oxide and the preparation method of the thermal insulation coating are the same as those in Example 4.
[0043] Comparative Example 3 A thermal insulation coating comprises the following ingredients, measured by weight: 22 parts of deionized water, 26 parts of a binder, 28 parts of a filler, 4 parts of a nano-composite material, 5 parts of graphene oxide, 8 parts of modified hollow glass microspheres, 2 parts of a freeze-thaw agent, 2 parts of a film-forming agent, 0.5 parts of a defoaming agent, 0.2 parts of a dispersant, and 0.5 parts of a thickener.
[0044] This comparative example 3 is based on Example 4, except that the modification operation in Examples 1-6 is not performed on graphene oxide, but it is directly incorporated; except for the above-mentioned different formulas, the preparation method of the modified hollow glass microspheres and the preparation method of the thermal insulation coating are consistent with Example 4.
[0045] Comparative Example 4 A thermal insulation coating comprises the following ingredients, measured by weight: 22 parts of deionized water, 26 parts of a binder, 28 parts of a filler, 4 parts of a nano-composite material, 5 parts of modified graphene oxide, 2 parts of a freeze-thaw agent, 2 parts of a film-forming agent, 0.5 parts of a defoaming agent, 0.2 parts of a dispersant, and 0.5 parts of a thickener.
[0046] This comparative example 4 is based on Example 4, except that the addition of modified hollow glass microspheres is omitted. Except for the above-mentioned different formulas, the preparation method of modified graphene oxide and the preparation method of thermal insulation coating are consistent with those of Example 4.
[0047] Comparative Example 5 A heat-insulating coating comprises the following ingredients, measured by weight: 22 parts of deionized water, 26 parts of a binder, 28 parts of a filler, 4 parts of a nano-composite material, 8 parts of modified hollow glass microspheres, 2 parts of a freeze-thaw agent, 2 parts of a film-forming agent, 0.5 parts of a defoaming agent, 0.2 parts of a dispersant, and 0.5 parts of a thickener.
[0048] This comparative example 5 is based on Example 4, except that the addition of modified graphene oxide is omitted. Except for the above-mentioned different formulas, the preparation method of the modified hollow glass microspheres and the preparation method of the thermal insulation coating are consistent with those of Example 4.
[0049] Comparative Example 6 A thermal insulation coating comprises the following ingredients, measured by weight: 22 parts of deionized water, 26 parts of a binder, 28 parts of a filler, 4 parts of a nano-composite material, 5 parts of modified graphene oxide, 8 parts of KH550 modified hollow glass microspheres, 2 parts of a freeze-thaw agent, 2 parts of a film-forming agent, 0.5 parts of a defoaming agent, 0.2 parts of a dispersant, and 0.5 parts of a thickener.
[0050] Specifically, the preparation and synthesis method of the KH550 modified hollow glass microspheres is as follows: 400g of deionized water, 3ml of hydrochloric acid, 11g of KH550, 10g of hollow glass microspheres, and 5ml of ethanol are added together into a three-necked flask, and continuous mechanical and ultrasonic stirring is performed, and the reaction is carried out and maintained at 40 degrees Celsius for 5 hours; then the product obtained by the reaction is washed in ethanol and deionized water for two rounds, respectively, and then dispersed; finally, the obtained product is dried at 100 degrees Celsius for 5 hours to prepare KH550 modified hollow glass microspheres.
[0051] This comparative example 6 is based on Example 4, except that hollow glass microspheres modified with KH550 are used. Except for the above-mentioned specific modification methods, the preparation methods of modified graphene oxide and thermal insulation coating are the same as those of Example 4.
[0052] Test example Thermal insulation performance test: The same cement asbestos board was used as the test board with a size of 150mm*70mm*5mm. According to the provisions of the standard GB / T9271-2008 "Standard Test Board for Paint and Varnish", the 150mm*70mm surface of the test board was brushed on one side. After the coating was completed, the test board was placed in a natural environment for 7 days, and the dry film thickness of the test board surface was uniformly coated to 250μm; When testing the thermal insulation performance, the test boards with different coatings prepared in Examples 1-6 and Comparative Examples 1-6 were embedded in styrene foam, and the side of the test board with the coating was set away from the styrene foam. A 275W heat light lamp was used to irradiate the coating directly, 30cm away from the coating, and the difference between the surface temperature and the back temperature of each test board of Examples 1-6 and Comparative Examples 1-6 was measured after 1h; Artificial aging resistance test: refer to GB / T 1865-2009 "Artificial weathering and artificial radiation exposure of paints and varnishes"; Tensile strength performance test: refer to JG / T172-2014 for testing; Elongation at break (under standard conditions) performance test: refer to JG / T172-2014 for testing; Washability test: GB / T 9266-2009 "Determination of washability of architectural coatings" was used as the washing medium, with deionized water. The data of the above test results are shown in Table 1.
[0053] Table 1 Comprehensive performance analysis: In the performance test table, tensile strength and elongation at break can characterize the flexibility and crack resistance of the coating film, especially in the process of dry-wet changes and high-low temperature changes, whether the coating is prone to cracking and damage can be characterized by the above indicators; in the performance test process, a higher elongation at break also indicates that the coating is more able to adapt to the deformation of the base surface and changes in temperature and humidity, prevent cracking and falling off, and is more suitable for application scenarios such as walls or facades. Examples 1-6 of the present application all have excellent thermal insulation and mechanical properties, and the anti-aging performance is also very excellent. The levels of coating powdering and coating discoloration have reached the excellent level of level 0.
[0054] In the formula components of Comparative Example 1, graphene oxide and hollow glass microspheres have not undergone any modification; although a stainless steel agitator is used in the coating preparation process, the two still cannot achieve a good dispersion effect and are prone to agglomeration in the thermal insulation coating; the thermal resistance performance is uneven, resulting in poor thermal insulation effect, and uneven dispersion may cause unstable material structure, which reduces the mechanical properties of the coating such as hardness, compression resistance, and impact resistance; therefore, the temperature difference, artificial aging resistance, tensile strength, elongation at break, and washability of Comparative Example 1 are all poor.
[0055] In Comparative Example 2, glass microspheres without any modification are added, and their various mechanical properties and thermal insulation properties are significantly different from those of Examples 1-6. The possible reason is that in Examples 1-6 of the present application, the hollow glass microspheres are modified by using trimethyltrivinylcyclotrisilane as a surface grafting agent, thereby successfully grafting double bonds on the surface of the glass microspheres, making the surface properties of the hollow glass microspheres more compatible with the base material of the thermal insulation coating, thereby improving the interfacial compatibility of the coating; and a strong interfacial interaction can be formed between the coating substrate and the modified hollow glass microspheres, thereby bringing about improvements in thermal insulation and mechanical properties.
[0056] In Comparative Example 3, graphene oxide that has not undergone any modification is added, and its various mechanical properties and thermal insulation properties are significantly different from those of Examples 1-6. The possible reason is that in Examples 1-6 of the present application, 1-amino-8-naphthol-3,6-disulfonic acid is introduced to modify and functionalize graphene oxide. The added sulfonic acid group and hydroxyl group after modification increase the hydrophilicity of the functionalized graphene oxide, making it better dispersible in the thermal insulation coating, and 1-amino-8-naphthol-3,6-disulfonic acid is attached to the surface of graphene. This attachment can help prevent the aggregation of graphene sheets, maintain the two-dimensional structure and performance of the functionalized graphene oxide, and help improve the thermal stability of the thermal insulation material.
[0057] Comparative Example 4 omits the addition of modified glass microspheres, and Comparative Example 5 omits the addition of modified graphene oxide; both are weaker than Comparative Example 2 and Comparative Example 3, indicating that only when modified graphene oxide and modified hollow glass microspheres are simultaneously incorporated into the thermal insulation coating can the above-mentioned beneficial effects be achieved.
[0058] Comparative Example 6 uses KH550 modified hollow glass microspheres commonly used in the art. Although its various performances are far superior to those of Comparative Examples 1-5, there is still a large gap between it and Examples 1-6. The possible reason is that in Examples 1-6 of the present application, modified graphene oxide and modified hollow glass microspheres are simultaneously introduced into the thermal insulation coating; only when the two work synergistically, the modified graphene oxide enhances the thermal stability of the thermal insulation coating, while the modified hollow glass microspheres enhance the thermal insulation coating's ability to block heat conduction. Under the synergistic effect of the two, the thermal insulation coating can avoid excessive heat conduction transfer, and at higher temperatures, it can still maintain good mechanical properties and thermal stability, thereby achieving a more excellent thermal insulation effect; and under the synergistic effect of the two, the anti-aging performance of the thermal insulation coating can also be significantly improved.
[0059] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A thermal insulation coating, characterized in that: The composition is as follows by weight: 10~30 parts of deionized water, 20~30 parts of binder, 15~36 parts of filler, 2~5 parts of nano-composite ingredients, 2~6 parts of modified graphene oxide, 5~10 parts of modified hollow glass microspheres, 1~2 parts of freeze-thaw agent, 1~3 parts of film-forming agent, 0.2~0.6 parts of defoaming agent, 0.1~0.3 parts of dispersant, and 0.3~0.6 parts of thickener.
2. A thermal insulation coating according to claim 1, characterized in that: The composition is as follows by weight: 22 parts of deionized water, 26 parts of binder, 28 parts of filler, 4 parts of nano-composite ingredients, 5 parts of modified graphene oxide, 8 parts of modified hollow glass microspheres, 2 parts of freeze-thaw agent, 2 parts of film-forming agent, 0.5 parts of defoaming agent, 0.2 parts of dispersant, and 0.5 parts of thickener.
3. A thermal insulation coating according to claim 1, characterized in that: The adhesive is a mixture of pure acrylic emulsion and styrene acrylic emulsion.
4. A thermal insulation coating according to claim 1, characterized in that: The filler is a mixture of titanium dioxide, sericite and talcum powder, and the mass ratio of the three is (10-22): (3-8): (2-6).
5. The thermal insulation coating according to claim 1, characterized in that: The nano composite material is a mixture of nano-SiO2 and nano-Zn, and the mass ratio of the two is 1:
1.
6. The thermal insulation coating according to claim 1, characterized in that: The freeze-thaw agent is any one of ethylene glycol and propylene glycol; the film-forming agent is any one of dodecyl alcohol ester and hexanediol butyl ether acetate.
7. The thermal insulation coating according to claim 1, characterized in that: The thickener is any one of hydroxypropyl methylcellulose and hydroxyethyl cellulose.
8. A thermal insulation coating according to any one of claims 1 to 7, characterized in that: The preparation and synthesis method of the modified graphene oxide is as follows: disperse graphite oxide in 250 ml of deionized water and perform ultrasonic treatment for 1 hour; dissolve 1-amino-8-naphthol-3,6-disulfonic acid in 10 ml of deionized water, and drop 2-3 drops of ammonia solution; then slowly drop the mixed solution into the fully dispersed graphite oxide; and stir thoroughly; after all the additions are made, heat to 70 degrees Celsius and stir for 24 hours; after stirring is completed, add hydrazine hydrate and heat to 100 degrees Celsius; continue stirring for 24 hours; The solution was then naturally cooled to room temperature, filtered with cellulose acetate membrane filter paper with a pore size of 0.1 micron, and washed multiple times with distilled water to obtain a water-dispersible black product. Finally, the black product was dried in a vacuum at 60 degrees Celsius for 72 hours to prepare the homemade modified graphene oxide.
9. A thermal insulation coating according to any one of claims 1 to 7, characterized in that: The preparation and synthesis method of the modified hollow glass microspheres is as follows: deionized water, hydrochloric acid, trimethyltrivinylcyclotrisilane, hollow glass microspheres, and ethanol are added together into a three-necked flask, and continuous mechanical and ultrasonic stirring is performed, and the reaction is carried out and maintained at 40 degrees Celsius for 5 hours; then the product obtained by the reaction is washed in ethanol and deionized water for two rounds, respectively, and then dispersed; finally, the obtained product is dried at 100 degrees Celsius for 5 hours to prepare the modified hollow glass microspheres.
10. A thermal insulation coating according to any one of claims 1 to 7, characterized in that: The preparation method of the thermal insulation coating is as follows: firstly, the nano-composite ingredients, modified graphene oxide, modified hollow glass microspheres and fillers are physically stirred and mixed to prepare a mixture A for standby use; then, deionized water, a binder, a filler, a freeze-thaw agent, a film-forming agent, a defoaming agent and a dispersant are added to a stainless steel stirring tank, and the mixture is mixed for 2 hours at a stirring speed of 800-1200 r / min; then, the mixture A is added to the stainless steel stirring tank at a stirring speed of 400-600 r / min; then, a thickener is added and stirred continuously for 1 hour; finally, the coating is filtered through a 100-120 mesh sieve to prepare the thermal insulation coating.
Citation Information
Patent Citations
A kind of heat-reflective and heat-insulating coating for recoating of building exterior wall and preparation method thereof
CN106118285B
Thermal-insulating external-wall coating of nano-composite water and its production
CN101029206A
Water-dispersion pigment red 57:1 modified pigment and preparation method thereof
CN108864752A
Heat preservation and heat insulation coating for glass surface and preparation method thereof
CN112831250A